Genome-Resolved Metaproteomic Analysis of Microbiota and Metabolic Pathways Involved in Taste Formation During Chinese Traditional Fish Sauce (Yu-lu) Fermentation - Wang, Yueqi; Wu, Yanyan; Li, Chunsheng; Zhao, Yongqiang; Xiang, Huan; Li, Laihao; Yang, Xianqing; Chen, Shengjun; Sun, Leilei; Qi, Bo (Frontiers in Nutrition, 2022)
Complex microbial metabolism is key to taste formation in high-quality fish sauce during fermentation. To guide quality supervising and targeted regulation, we analyzed the function of microbial flora during fermentation based on a previous metagenomic database. Most of the identified genes involved in metabolic functions showed an upward trend in abundance during fermentation. In total, 571 proteins extracted from fish sauce at different fermentation stages were identified. The proteins were mainly derived from Halanaerobium, Psychrobacter, Photobacterium, and Tetragenococcus. Functional annotation showed 15 pathways related to amino acid metabolism, including alanine, aspartate, glutamate, and histidine metabolism; lysine degradation; and arginine biosynthesis. This study provides a theoretical basis for the taste formation mechanisms during traditional fish sauce fermentation.